Investigation of optical detection strategies for transabdominal fetal heart rate detection using three-layered tissue model and Monte Carlo simulation - Gan, K.B.; Zahedi, E.; Mohd Ali, M.A. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
In this paper, the Monte Carlo technique is used to determine the optical detection strategies in three-layered (maternal, amniotic fluid and fetal) tissue model. This model is utilized to estimate the transabdominal optical power and optimum source–detector (S–D) separation. Results based on the launching of 2 million photons with 1 mW optical power showed that the expected optical power output is in the range of 10–6–10–10 W/cm2 depending on S–D separation. Considering the limit of the signal processing methods (such as adaptive noise cancelling) and the use of silicon photodetector, an S–D separation of 4 cm has been selected as a practical compromise between signal level and percentage of optical power (70%) coming from the fetal layer. Based on these findings, transabdominal fetal heart rate detection system using NIR and adaptive filtering can be designed and developed.
Optica Applicata, Vol. 41, 2011, Nr 4, s. 885-896
Keywords: optyka; transabdominal; fetal heart rate; Monte Carlo simulation; tissue model